P-526 Targeting histone modifications: H3K27 acetylation regulates the expression of genes involved in key processes of uterine leiomyoma pathogenesis. (30th June 2022) - Carbajo-García, M C; de Miguel-Gómez, L; Juárez-Barber, E; Trelis, A; Monleón, J; Pellicer, A; Flanagan, J; Ferrero, H
Abstract: Study question: Does histone mark H3K27ac regulate the expression of genes involved in uterine leiomyoma (UL) pathogenesis, and can histone deacetylation inhibition be a new therapeutic approach? Summary answer: H3K27ac regulates genes implicated in UL pathogenesis through angiogenesis and extracellular matrix (ECM), and histone deacetylation reversion could offer a therapeutic approach to treat UL. What is known already: UL is a benign tumor arising from myometrium (MM). Women present symptoms such as pelvic pain and infertility. There is no fully effective treatment with minimal side effects. Available medical options focus on the relief of symptoms and not in mechanisms implicated in UL development. Histone modifications are altered in tumors, particularly via histone acetylation which is correlated with gene activation. Herein, we aimed to identify if the modification H3K27ac is involved in UL pathogenesis, determining the relationship between H3K27ac and gene expression in UL versus MM and if its reversion may be a therapeutic option to treat UL. Study design, size, duration: Prospective study comparing transcriptome (GEO:GSE192354 and GSE142332) by RNA sequencing (RNA-seq) (n = 48) and H3K27ac profile (GEO:GSE142332) by Chromatin Immunoprecipitation Sequencing (CHIP-seq) (n = 19) in UL versus adjacent MM tissue. Human uterine leiomyoma primary (HULP) cells obtained from individual patients (n = 10) were treated with 0.01% DMSO (control) and 10 µM SAHA, a histone deacetylases inhibitor, for 48 hours. Participants/materials, setting, methods: Samples were collected from 48 women aged 31-54 years. Bioinformatics analysis were performed within the R/Bioconductor (4.1.1.). Differential expressed genes (DEGs) were analysed using three methods: DESeq2, edgeR and limma. Common DEGs (FDR<0.01, log2FC>1 or <-1) were considered for further analysis. Differential H2K27ac peak enrichment analysis of selected genes was performed with limma and functional enrichment analysis (FDR<0.05) with Shiny Go (version 0.741). SAHA effect on hypoacetylated/downregulated genes was assessed in HULP cells by qRT-PCR. Main results and the role of chance: CHIP-seq analysis showed a lower amount of global H3K27ac peak enrichment level in UL versus MM (p-value<2.2e-16). RNA-seq showed 922 common DEGs in UL versus MM, being 559 up-regulated and 363 down-regulated (FDR<0.01, log2FC>1 or <-1). Integration of CHIP-seq and RNA-seq data showed that among 922 selected genes, 482 also presented the histone mark H3K27ac. Differential peak enrichment analysis demonstrated that 82 of them presented differential acetylation (FDR<0.05) in UL versus MM, being 29 hyper-acetylated/up-regulated and 53 hypo-acetylated/down-regulated. Functional enrichment analysis of 82 DEGs regulated by H3K27ac showed biological processes deregulated in UL that were related to angiogenesis. Additionally, we found cellular components enriched in UL, which were related to an alteration of ECM, one of the key features of UL. We studied further these 82 genes controlled by H3K27ac and found hyperacetylation/upregulation of oncogenes ( NDP, TFAP2C, HOXA13, COL24A1 and IGFL3 ) and hypoacetylation/downregulation of tumor suppressor genes ( CD40, GIMAP8, IL15, GPX3 and DPT ) in UL, which are related to immune system, angiogenesis, invasion, metabolism, ECM, TGFβ3 and Wnt/β-catenin pathway dysregulation. Finally, SAHA treatment in HULP cells significantly increased expression of the tumor suppressor genes that were hypoacetylated/downregulated in UL versus MM ( CD40, GIMAP8, IL15, GPX3 and DPT ) (p < 0.05). Limitations, reasons for caution: This is a preliminary study including only 19 participants in ChIP-seq analysis, thereby we should be cautious extrapolating our results to the general population. Further studies are necessary to determine the effectiveness of histone deacetylases inhibition, SAHA dose and adverse effects on UL in vivo. Wider implications of the findings: H3K27 acetylation regulates the expression of oncogenes and tumor suppressor genes involved in key processes of UL pathogenesis, such as angiogenesis and ECM formation. Histone deacetylation reversion by SAHA upregulated the expression of tumor suppressor genes in HULP cells, suggesting histone deacetylation as a potential therapeutic approach for UL patients. Trial registration number: Not applicable